2021
DOI: 10.3168/jds.2020-20002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peripartal yeast culture supplementation on lactation performance, blood biomarkers, rumen fermentation, and rumen bacteria species in dairy cows

Abstract: Feeding yeast culture fermentation products has been associated with improved feed intake and milk yield in transition dairy cows. These improvements in performance have been further described in terms of rumen characteristics, metabolic profile, and immune response. The objective of this study was to evaluate the effects of a commercial yeast culture product (YC; Culture Classic HD, Phibro Animal Health) on performance, blood biomarkers, rumen fermentation, and rumen bacterial population in dairy cows from −3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 70 publications
(119 reference statements)
1
19
0
Order By: Relevance
“…Thus, the decreased concentration of valeric acid following yeast supplementation may be related to the down-regulation of Megasphaera ( Supplementary Table 5 ). However, Malekkhahi et al (2016) and Carpinelli et al (2021) reported that ADY and YC supplementation tended to increase the relative abundance of Megasphaera in dairy cows. The cause of these inconsistent findings needs to be explored but may be related to the status of the experimental animals or dietary composition.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the decreased concentration of valeric acid following yeast supplementation may be related to the down-regulation of Megasphaera ( Supplementary Table 5 ). However, Malekkhahi et al (2016) and Carpinelli et al (2021) reported that ADY and YC supplementation tended to increase the relative abundance of Megasphaera in dairy cows. The cause of these inconsistent findings needs to be explored but may be related to the status of the experimental animals or dietary composition.…”
Section: Discussionmentioning
confidence: 97%
“…The rumen of dairy cows is a stable ecosystem that provides a good metabolic environment for microbes, and maintaining its stability is of great significance ( Carpinelli et al., 2021 ). Further, NH 3 –N in the rumen of dairy cows, which is primarily generated by the degradation of ingested protein nitrogen and non-protein nitrogen, is the main nitrogen source for microbial protein synthesis ( Nasrollahi et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ruminal microorganisms can produce short-chain fatty acids by fermenting carbohydrates such as cellulose and hemicellulose, which are the primary source of energy for ruminants, achieving more than 50% of their energy requirements [ 56 ]. Previous studies have shown that Bacteroidota and Firmicutes are the dominant phylum in the deer family [ 25 , 31 , 57 ], and they are also the most central ruminal bacteria with the most significant percentage of abundance in other ruminants, such as dairy cows [ 58 ].…”
Section: Discussionmentioning
confidence: 99%